Christliches Leben und die Verbesserung des Menschen Enhancement und Heiligung bei Calvin - Felder, Matthias (Theologische Bibliothek Töpelmann, 2022)
Self-optimization is all the rage. What do theology and the church have to say about it? Should they issue a warning and strike up a cultural pessimistic tune? Maybe they could activate their own resources, which have the potential for discursive compatibility with phenomena of self-improvement. This study brings the discourse of enhancement into dialogue with the locus of healing in Calvin.